DESIGN OF MONITORING MOVEMENT PERSONNEL IN THE NIGHT DAY - Setiawan, Aries Boedi; Pasanenda, Bovi (JEEMECS (Journal of Electrical Engineering, Mechatronic and Computer Science), 2018)
Night patrols were conducted in groups of squads, a squad of ten men consisting of a squad commander and nine squad personnel. In an exercise or in the actual field of operation in the movement of a team, a squad leader is responsible for the movement of his personnel, for example in the movement of the squad on night patrols with dark conditions and limited visibility, the team commanders will have difficulty in monitoring their personnel one by one in the movements concurrent in a particular formation according to the instructions of the squad commanders. A commander is responsible for his personnel when one of his personnel is lost or lost. Because a squad commander in the field of operation or training should minimize both personnel and material losses. To overcome this problem, a monitoring tool for the movement of squad personnel in night patrols utilizes the transmit distance from the XBee module and consists of a voltage-lowering circuit and a series of microcontrollers that act as an on-off controller on the led. The workings of this tool is based on microcontroller. The programming language used is the basic programming language compiler that is filled on an IC chip. The purpose of making this tool for the effectiveness of the use of electronic devices and reduce the loss of personnel and matrix in carrying out the actual training tasks and field operations tasks.Based on the results of design, manufacture, testing and operation obtained minimal error so that it can be stated that the monitoring tool movement of personnel squads on night patrol can work in accordance with good conditions and can be applied into the actual form.DOI :Â https://doi.org/10.26905/jeemecs.v1i1.2302